"Paying with my face" – Understanding users' adoption and privacy concerns of facial recognition payment. (September 2022) - Liao, Mengqi; Agnihotri, Devanshi; Zhong, Xinliang
Facial recognition payment (FRP) is a widely adopted technology in countries outside of the United States (US), particularly in east Asian countries. However, FRP is still not widely accepted and implemented within the US, partly due to users' privacy concerns of FRP. In our survey study of 164 US participants, we adopted the extended Technology Acceptance Model (TAM) to investigate the relationship between users' privacy concerns, power usage, attitudes, and their intentions of adopting FRP. Our findings showed significant relationships among these assessed variables and indicated that privacy concerns was indeed an important factor in predicting individuals' intentions of adopting FRP, but power users might become early adopters that could spearhead widespread acceptance of FRP within the US due to their lessened privacy concerns.